Functional characterization and expression patterns of PnATX genes under different abiotic stress treatments in Populus. (6th February 2020) - Xu, Zhiru; Huang, Jiahuan; Qu, Chunpu; Chang, Ruhui; Chen, Jinyuan; Wang, Qi; Xi, Qi; Song, Yang; Sun, Qi; Yang, Chuanping; Liu, Guanjun
Abstract: The copper chaperone ATX1 has been investigated previously in the herbaceous plants Arabidopsis and rice. However, the molecular mechanisms of ATX1 underlying copper transport and functional characteristics in the woody plant Populus are poorly understood. In this study, PnATX1 and PnATX2 of Populus simonii × P. nigra were identified and characterized. Sequence analysis showed that PnATXs contained the metal-binding motif MXCXXC in the N-terminus and a lysine-rich region. Phylogenetic analysis of ATX protein sequences revealed that PnATXs were clustered in the same group as AtATX1. PnATX proteins were localized in the cytoplasm and nucleus. Tissue-specific expression analysis showed that PnATX1 and PnATX2 were expressed in all analyzed tissues and, in particular, expressed to a higher relative expression level in young leaves. Quantitative real-time PCR analysis indicated that each PnATX gene was differentially expressed in different tissues under treatments with copper, zinc, iron, jasmonate and salicylic acid (SA). The copper-response element GTAC, methyl jasmonate and salicylic acid responsiveness elements and other cis -acting elements were identified in the PnATX1 and PnATX2 promoters. Expression of β-glucuronidase driven by the PnATX1 promoter was observed in the apical meristem of 7-day-old Arabidopsis transgenic seedlings, and the signal strength was not influenced by deficient or excessive copper conditions. Both PnATX1 and PnATX2 functionally rescued the defective phenotypes of yeast atx1Δ and sod1Δ strains. Under copper excess and deficiency conditions, transgenic Arabidopsis atx1 mutants harboring 35S:: PnATX constructs exhibited root length and fresh weight similar to those of the wild type and higher than those of Arabidopsis atx1 mutants. Superoxide dismutase activity decreased in transgenic lines compared with that of atx1 mutants, whereas peroxidase and catalase activities increased significantly under excess copper. The results provide a basis for elucidating the role of Populus PnATX genes in copper homeostasis.